Analysis of worst case Power system contingencies using vulnerability frontier - Dawar, Vikas (My University, 2010)
One of the most important aspect in a power system network is to make a network secure against unanticipated events. In general, a power system network is always made N-1 secure: any single outage will not lead to instability in a network. The electrical transmission system is vulnerable to extreme events which can cascade resulting in blackouts. In this thesis, we identify critical corridors, subsets of those transmission lines that are most vulnerable to extreme events. It is computationally difficult to take into account all possible multiple outages of lines. In this thesis, we consider the worst case scenario in which the outages of a particular subset of transmission lines result in maximum power imbalance. Subsets of transmission lines that appear with higher frequencies are candidates for detailed study as they may lead to extreme events. We present a vulnerability frontier (graph between number of lines cut and maximum power imbalance corresponding to those lines cut) for 30, 118, 179, 225 and 1553 bus system. Tables listing the frequencies at which a particular cut-set of transmission lines (for 30,118 and 179 bus system) occur have also been presented.